The impact of culture shock on intention to quit among the Malaysian Army recruits: Does mentorship matter? / Faizi Zulkifli - Faizi , Zulkifli (2021)
Intention to quit among employee is becoming progressively vital and understanding why intention to quit happen is a very important issue that needs to be tackled by the organisation. The present study looks into the issue of intention to quit among recruits in the Basic Army Training Centre, Port Dickson. Malaysian Army has wasted a lot of money and time when this happens to this training establishment. The impact of Culture Shock and Intention to Quit is examined in the military context. The study was conducted in two phases (Phase I – Preliminary Study and Phase II – Questionnaire Survey). Phase I – Preliminary Study was conducted with fifteen participants – five from the dismissed recruits, five from recruits that passed the training and five instructors. This preliminary study aimed to explore what is the actual cause of this phenomenon. A content analysis of open-ended questions and interview data identified five themes: Culture Shock, Stress, Frustration, Fatigue and Disorientation. Importantly, five themes that emerged were the main cause of Intention to Quit in this study and was well represented in ABC Culture Shock Theory. Subsequently, this finding was used to develop a research framework for Phase II – Questionnaire Survey. Phase II – Questionnaire Survey was conducted with four hundred respondents during the earlier stage of their training. The data collected was then analysed by using Statistic Package of Social Sciences Version 25 (SPSS ver. 25) and Partial Least Square – Sequential Equation Model (PLS – SEM). SPSS was used to validate the data normality and descriptive analysis. Meanwhile, PLS – SEM was used to analyse the relationship of all the constructs that were hypothesised. Before the hypotheses testing was conducted, the reflective measurement model and structural model assessment were conducted. The results showed that all testings were in the acceptable parameter. The PLS – SEM results showed that out of the seventeen hypotheses, thirteen hypotheses were supported and three hypotheses were not supported namely: the relationship between Fatigue and Intention to Quit, Fatigue mediate the relationship between Culture Shock and Intention to Quit, and Mentorship moderate the relationship between Stress and Intention to Quit. The research provides useful insight into the effect of Culture Shock and Intention to Quit, particularly in the military context. It is anticipated that the finding of this research will contribute to the Malaysian Army Headquarters as they tackle the issue of Culture Shock among recruits that lead to Intention to Quit. Finally, study implication, limitation, future research and conclusion are highlighted.